Clinical risk stratification in patients with surgically resectable micropapillary bladder cancer. (11th November 2016) - Fernández, Mario I.; Williams, Stephen B.; Willis, Daniel L.; Slack, Rebecca S.; Dickstein, Rian J.; Parikh, Sahil; Chiong, Edmund; Siefker‐Radtke, Arlene O.; Guo, Charles C.; Czerniak, Bogdan A.; McConkey, David J.; Shah, Jay B.; et al.
Abstract : Objective: To analyse survival in patients with clinically localised, surgically resectable micropapillary bladder cancer (MPBC) undergoing radical cystectomy (RC) with and without neoadjuvant chemotherapy (NAC) and develop risk strata based on outcome data. Patients and Methods: A review of our database identified 103 patients with surgically resectable (≤cT4acN0 cM0) MPBC who underwent RC. Survival estimates were calculated using Kaplan–Meier method and compared using log‐rank tests. Classification and regression tree (CART) analysis was performed to identify risk groups for survival. Results: For the entire cohort, estimated 5‐year overall survival and disease‐specific survival (DSS) rates were 52% and 58%, respectively. CART analysis identified three risk subgroups: low‐risk: cT1, no hydronephrosis; high‐risk: ≥cT2, no hydronephrosis; and highest‐risk: cTany with tumour‐associated hydronephrosis. The 5‐year DSS for the low‐, high‐, and highest‐risk groups were 92%, 51%, and 17%, respectively ( P < 0.001). Patients down‐staged at RC <pT1 regardless of the use of NAC had the best survival (5‐year DSS of 96% vs 45% for those not down‐staged; P < 0.001), while those who were not down‐staged despite NAC had 5‐year DSS of only 17%. Conclusion: In patients with surgically resectable MPBC, NAC appears to confer benefit to patients with muscle‐invasive disease without hydronephrosis, while patients with cT1 disease can proceed to upfront RC. Patients with hydronephrosis do not appear to respond well to NAC and have poor prognosis regardless of treatment paradigm. However, further external validation studies are needed to support the proposed risk stratification before treatment recommendations can be made.